The Comparission Three Structure Of Cost 251 Using Tlm Method - Muhammad Ikhwanus (Faculty of Engineering, Malikussaleh University, 2018)
The Transmission Line Matrix (TLM) was formulated and represented in the time domain. The main issue of approach in time domain analysis is the efficiency of computation to model non linear characteristic in time domain rather than in frequency domain. In this research, a TLM approach in the time domain analysis will be introduced to solve the III-V single rib waveguide structure that had been finished by previous researchers. The approach method is based on a huygen’s principle using shunt mode equivalent circuit representation in the inhomogeneous material to solve scalar wave equation. Propagation constants can be obtained by solving eigen value, β, of scalar wave equation. Consequently, by setting the suitable mesh size, the result of TLM can provide more accurate and stability modeling for wave propagation compared with the other methods. The accuracy and stability of TLM will be presented in this research.